ANALISIS HUKUM PENGELOLAAN WAKAF UANG DI INDONESIA (KESENJANGAN REGULASI, DIGITALISASI, DAN URGENSI REFORMASI KELEMBAGAAN) - Suarjana Suarjana (Universitas Islam Negeri Mataram, 2026)
This research is motivated by the problematic implementation of cash waqf management in Indonesia, which has not been optimal despite its significant potential as an instrument for community economic empowerment. Cash waqf has grown from Rp61.2 billion in 2019 to Rp571.8 billion in 2024, yet this remains far below the estimated annual potential of Rp180 trillion. This study analyzes the legal framework governing cash waqf management in Indonesia, identifies institutional and regulatory problems, and proposes normative solutions. The research examines the gap between regulatory mandates requiring cash waqf to be channeled through Islamic Financial Institutions-Cash Waqf Recipients (LKS-PWU) and community practice that directly entrusts funds to nazhir institutions. The legal framework established through Law No. 41/2004, Government Regulation No. 42/2006, BWI Regulation No. 1/2020, and PMA No. 14/2025 has provided foundational legitimacy and procedural guidance. However, significant legal vacuums remain: first, Article 17's physical presence requirement renders electronic waqf contracts legally uncertain; second, no dedicated consumer protection exists for waqif funds on non-bank fintech platforms; and third, absent interoperability standards between national payment infrastructure and digital waqf platforms impede oversight. The research method used was a normative juridical approach with qualitative analysis of legal documents and scholarly literature published 2021–2025. The results indicate that cash waqf management faces three primary legal problems: (1) regulatory mismatch between physical presence requirements and digital transactions; (2) suboptimal institutional performance of LKS-PWU and nazhir institutions; and (3) absence of comprehensive technical regulations for innovative instruments. Grounded in maqasid al-shari'ah, closing these vacuums constitutes a substantive Islamic obligation rooted in hifzh al-mal and maslahah. This study recommends an integrative approach between positive law and Sharia principles through regulatory reform and institutional capacity building.